The Increasing Prevalence in Intersex Variation from Toxicological Dysregulation in Fetal Reproductive Tissue Differentiation and Development by Endocrine-Disrupting Chemicals - Alisa L. Rich; Laura M. Phipps; Sweta Tiwari; Hemanth Rudraraju; Philip O. Dokpesi (SAGE Publishing, 2016)
An increasing number of children are born with intersex variation (IV; ambiguous genitalia/hermaphrodite, pseudohermaphroditism, etc.). Evidence shows that endocrine-disrupting chemicals (EDCs) in the environment can cause reproductive variation through dysregulation of normal reproductive tissue differentiation, growth, and maturation if the fetus is exposed to EDCs during critical developmental times in utero. Animal studies support fish and reptile embryos exhibited IV and sex reversal when exposed to EDCs. Occupational studies verified higher prevalence of offspring with IV in chemically exposed workers (male and female). Chemicals associated with endocrine-disrupting ability in humans include organochlorine pesticides, polychlorinated biphenyls, bisphenol A, phthalates, dioxins, and furans. Intersex individuals may have concurrent physical disorders requiring lifelong medical intervention and experience gender dysphoria. An urgent need exists to determine which chemicals possess the greatest risk for IV and the mechanisms by which these chemicals are capable of interfering with normal physiological development in children.